FOOD SAFETY ASPECTS IN BLOOD COCKLES (Tegillarca granosa) CULTURED OFF SELANGOR, PENINSULAR MALAYSIA - M.N, Wan Norhana; Yurimoto, T.; Intan Nurlemsha, B.; Saadon, K. (Malaysian Journal of Science, 2016)
This study evaluates some food safety aspects of the blood cockle (Tegillarca granosa) and its culture waters at Bagan Nakhoda Omar (BNO), Sungai Besar (SB) and Bagan Sungai Buloh (BSB) in Selangor. Samplings of cockles and seawater from the culture beds were carried out from Oct 2014 to Mar 2015 to analyse for fecal indicator bacteria, hepatitis A virus and saxitoxin in cockles and harmful phytoplankton and heavy metals in seawater. The results indicated that cockles from BNO, SB and BSB were of Class C category suggesting that the cockles could only be sold for human consumption after re-laying, followed by purification or heat treatment processes. Meanwhile, the cockle culture areas of BNO, SB and BSB were classified as ‘conditionally approved’. The saxitoxin levels in cockle samples from BNO, SB and BSB were 0.12-0.80, 0.05-0.25 and 0.05-0.18 nmol/g, respectively and hepatitis A virus was not detected in the cockels samples. Phytoplankton composition was dominated by the diatom group (>96%). Pseudo-nitzhia spp. and Dinophysis caudata were commonly found but at low cell counts. The levels of Cr, Zn, Cu, As and Hg were higher than the Malaysian standards while Se, Cd and Pb were within the safe limits. Further investigation should be carried out to identify the pattern and source of pollution throughout a year so that appropriate and cost-effective corrective actions could be taken to prevent future pollution and adverse effect to the public. Keywords: food safety, phytoplankton, cockles, culture waters, Selangor